We motivate, you lead / Nor Syamaliah Ngah, Azila Ayob and Norazlin Abd Aziz - Ngah, Nor Syamaliah; Ayob, Azila; Abd Aziz, Norazlin (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Education is one of the key determinants in producing competent leaders (Ausat & Suherlan, 2021). Thus, it is crucial for schools to implement leadership education programs in order to develop school students' moral character and leadership abilities. With the aid of this strategy, school students can better comprehend the principles of leadership, hone their cooperation and communication abilities, and obtain actual experience in managing teams or organisations (Khairani, 2022). However, few and poorly coordinated leadership education initiatives are still being used in schools (Cahyon et al., 2023). According to the school prefect’s teachers at SMK Sentosa, Kampar, Perak, due to teachers' busy schedules and the small number of possibilities for school students to exhibit their capabilities, the school does not provide adequate chances for school students to build their leadership abilities. School students may not benefit fully from the curriculum since some schools still view leadership development as an optional extra that is not particularly significant.